Plasma Biochemical Profile Of Murrah Buffaloes (Bubalus bubalis) Fed Peripartum Positive Dietary Cation Anion Difference Diet - Arora, A.; Singh, P.; Dhindsa, S. S.; Grewal, R.S.; Singh, N.; Honparkhe, M.; Malik, V. S. (The Indian Journal of Animal Reproduction, 2021)
A comparative study was done to evaluate peripartum Dietary Cation-Anion Difference (DCAD) feeding in buffaloes. Murrah buffaloes (n=25) were randomly divided into three groups: Group 1 (n=10), Group 2 (n=10) and Group 3 (n=5, control). Buffaloes in Group 1 and Group 2 were fed DCAD levels of -100 mEq 100 g-1 of dry matter (DM) starting 30 days prepartum. During the postpartum period and upto 30 days, Group 1 was fed on DCAD levels of +300 mEq 100 g-1 and Group 2 was fed DCAD levels of +400 mEq 100 g-1. Group 3 (control) buffaloes were fed standard diet without any cationic or anionic salts. Blood sampling was carried out on day -7, 0, 20, 26, 32, 38, 45, 52 and 54 of calving. Plasma urea nitrogen (PUN) in Group 1, 2 and 3 buffaloes ranged from 16.5±0.88 to 18.3±0.68 mg dl-1, 16.0±0.40 to 17.8±0.47 mg dl-1 and 15.4±0.79 to 22.0±0.86 mg dl-1, respectively. PUN after 26 days postpartum was significantly low (P< 0.05) in buffaloes fed on two different DCAD levels than the control group. Creatine Kinase (CK) activity in Group 1, 2 and 3 buffaloes ranged from 175.22±15.4 to 241.44±21.9 UL-1, 192± 23.26 to 575.75±162.05 UL-1 and 187.6±92.75 to 319±50.06 UL-1, respectively. In Group 2, CK activity was significantly higher (P< 0.05) as compared to group 1 and group 3 across 38 and 54days postpartum. Creatinine in Group 1, 2 and 3 buffaloes ranged from 1.56±0.12 to 2.21±0.14 mg dl-1, 1.70±0.08 to 2.58±0.23 mgdl-1 and 1.84±0.17 to 2.22±0.29 mg dl-1, respectively. In Group 3, creatinine was significantly higher (P< 0.05) than group 1 across day 20, 52 and 54 postpartum. Glucose levels in Group 1, 2 and 3 buffaloes ranged from 67.55±2.84 to 99.44±8.00 mgdl-1, 67.00±2.97 to 110.87±8.49 mgdl-1 and 68.00±5.34 to 93.4±10.74 mg dl-1, respectively. Glucose levels were significantly higher (P< 0.05) in Group 3 than group 1 and group 2 across 38, 52 and 54 day postpartum. Total protein concentration in Group 1, 2 and 3 buffaloes ranged from 6.65±0.36 to 9.61±0.33 gdl-1, 6.46±0.32 to 10.06±0.56 gdl-1 and 9.02±0.41 to 10.06±0.46 gdl-1, respectively. Total protein levels were